2021
DOI: 10.1037/hea0001115
|View full text |Cite
|
Sign up to set email alerts
|

Integrating headache trigger management strategies into cognitive-behavioral therapy: A randomized controlled trial.

Abstract: Objective: Traditionally, the standard advice to individuals suffering from migraine and tension-type headache was that the best way to prevent headaches is to avoid the triggers. This advice has been challenged in recent years and the Trigger Avoidance Model of Headache has been proposed, which suggests that one pathway to developing a headache disorder is by avoiding triggers resulting in trigger sensitization. The objective of the study was to evaluate a novel intervention for primary headache comprising a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…No effect of study phase was found for headache frequency and severity or ictal photophobia, probably due to the high variability in the patients’ treatment responses. In the LCT approach, the trigger exposure treatment was conducted for 8 weeks and completed with cognitive-behavioral and relaxation techniques [ 13 , 15 ]. With only one week, the duration of the interventions was probably too short to produce significant clinical improvements in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No effect of study phase was found for headache frequency and severity or ictal photophobia, probably due to the high variability in the patients’ treatment responses. In the LCT approach, the trigger exposure treatment was conducted for 8 weeks and completed with cognitive-behavioral and relaxation techniques [ 13 , 15 ]. With only one week, the duration of the interventions was probably too short to produce significant clinical improvements in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Trigger exposures were accompanied by several methods of cognitive-behavioral therapy (education, management of dysfunctional thoughts, relapse prevention strategies) and relaxation training. When compared to an untreated waiting list, patients with recurrent headaches receiving LCT showed reduced headache and medication consumption, whereas for trigger avoidance combined with cognitive-behavioral therapy no effect was found [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of behavioral treatments have been shown to differ by type of treatment. For example, cognitive behavioral therapies lead to reductions in attack frequency and disability, [3][4][5][6] whereas mindfulness-based therapies have usually reduced only disability (with one recent exception, which included a four-session migraine-focused behavioral intervention). [7][8][9] Even within a modality, such as CBT for depression, effect sizes become larger as therapist interaction increases.…”
Section: Do Behavioral Treatments Work For Migraine Prevention?mentioning
confidence: 99%
“…Cognitive factors, such as fear and avoidance of pain and pain catastrophizing, have demonstrated strong relationships with pain interference and quality of life [ 6 8 ]. Interventions that focus on identifying and restructuring maladaptive pain cognitions have demonstrated efficacy in improving pain-related quality of life [ 9 12 ]. Incorporating behavioral management of chronic pain and headache disorders improves outcomes beyond medical management alone [ 13 15 ].…”
Section: Advances In Behavioral Management Of Pain and Headache Disor...mentioning
confidence: 99%